Crystal Structure of 4-({(1E,2E)-3-[3-(4-fluorophenyl)-1- isopropyl-1H-indol-2-yl]allylidene}amino)-5-methyl-1H-1,2,4-triazole-5(4H)-thione - Kulkarni, Ajaykumar D.; Lutfor, M. R.; M. M., Yusoff; Huey, Chong Kwong; Ching, Kheng Quah (International Union of Crystallography, 2015)
The title compound, C23H22FN5S, exists in a trans conformation with respect to the methene C C and the acyclic N C bonds. The 1,2,4-triazole-5(4H)-thione ring makes dihedral angles of 88.66 (9) and 84.51 (10), respectively, with the indole and benzene rings. In the crystal, molecules are linked by pairs of N—H S hydrogen bonds, forming inversion dimers with an R2 2(8) ring motif. The dimers are linked via C—H interactions, forming chains along [110]. The chains are linked via — interactions involving inversion-related triazole rings [centroid–centroid distance = 3.4340 (13) A ˚ ], forming layers parallel to the ab plane.